PELAKSANAAN BIMBINGAN INDIVIDUAL / KELOMPOK TERHADAP SISWA SD DENGAN PERMASALAHAN - Sianipar, Chindi Claudia; Ginting, Ika Lia Perbina; Sihombing, Milantina; Purba, Shyntia; Sinaga, Yessi Intana (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
Learning motivation is a key factor in determining student success in the educational process. However, many students face various obstacles that cause low learning motivation, both from internal factors such as low self-confidence and academic ability, and external factors such as pressure from the family environment and lack of social support from peers. This study aims to describe the process and results of the implementation of individual guidance services for an elementary school student who experiences learning motivation problems. The method used is a case study with a qualitative approach. Data were obtained through interviews. The results of the implementation of individual guidance showed an increase in student learning motivation, which was reflected in increased active participation in class, courage to communicate, and initiative in asking for help when experiencing learning difficulties. In addition, the implementation of this guidance also showed the importance of the role of empathy, patience, and student involvement in building effective counseling relationships. These findings confirm that individual guidance services can be an effective intervention in increasing student learning motivation, as well as a means of professional development for prospective teacher mentors.